Beyond the politics of labelling: exploring the cessation clauses for Rwandan and Eritrean refugees through semiotics - Cole, G (2016)
Academics have for decades written on the need to interrogate the labels upon which the field of Refugee and Forced Migration Studies has been founded. At the centre of these discussions has been theorising around the 'integrity' and 'content' of the refugee label itself, with foundational texts expounding the need to take nothing about the meaning and purpose of this label for granted. This is evidently important in popular accounts, where the term's misuse fuels anti-immigrant sentiments and societal mistrust, as well as for the futures of these populations, as multiple interpretations of their status affect attempts to negotiate durable solutions to their plight. Without denying the importance of these theoretical accounts, or the incredibly rich literature that has emerged on account of them, this thesis suggests that much of the theorising on labelling to date has lacked a clear theoretical framework around which to structure otherwise critical observations vis-à-vis the performative and malleable characteristics of language. It therefore introduces semiotic theories and methodologies as an approach for making sense of these manifold interpretations and their relationships to each other, and to explore what impacts this has on negotiations over refugees' futures. Associated theories are used to explain the controversial negotiations that surrounded the invocation of the Cessation Clause for Eritrean refugees in Sudan in 2002, and the ongoing attempts to apply Cessation to Rwandan refugees in Uganda. Both processes were mired by controversy, and yet almost no literature exists detailing when, why and how they unfolded as they did. Disaggregating the refugee 'label' through the semiotic frameworks provided by Saussure and Barthes helps explain the conceptual and spatial dissonance that plagued attempts to conclude these protracted refugee situations. Through doing so, this thesis seeks to make three main contributions. First, it provides these extended accounts of how decisions to apply Cessation are arrived at, thereby filling an empirical gap in literature on this process. Second, it presents a heuristic framework rooted in linguistic theories to explain how certain words and objects – including the refugee label - can see their meanings transformed and bourgeon over time, the mechanisms through which this distortion occurs and is accommodated within discussions over the treatment of refugees, and the implications that the application of this theoretical framework has for how we understand particular incidents of decision-making within the refugee regime. Third, these theoretical approaches are shown to result in key challenges to how the role, content and function of the word refugee have been conceptualised to date.